Uncovering the Role of Bicarbonate in Calcium Carbonate Formation at Near-Neutral pH - Huang, Y.C.; Rao, A.; Huang, S.J.; Chang, C.Y.; Drechsler, M.; Knaus, J.; Chan, J.C.C.; Raiteri, Paolo; Gale, Julian; Gebauer, Denis (WILEY-V C H VERLAG GMBH, 2021)
Mechanistic pathways relevant to mineralization are not well-understood fundamentally, let alone in the context of their biological and geological environments. Through quantitative analysis of ion association at near-neutral pH, we identify the involvement of HCO3− ions in CaCO3 nucleation. Incorporation of HCO3− ions into the structure of amorphous intermediates is corroborated by solid-state nuclear magnetic resonance spectroscopy, complemented by quantum mechanical calculations and molecular dynamics simulations. We identify the roles of HCO3− ions as being through (i) competition for ion association during the formation of ion pairs and ion clusters prior to nucleation and (ii) incorporation as a significant structural component of amorphous mineral particles. The roles of HCO3− ions as active soluble species and structural constituents in CaCO3 formation are of fundamental importance and provide a basis for a better understanding of physiological and geological mineralization.